Silicon-induced general, mild, and efficient one-pot, three-component synthesis of amidoalkyl naphthol libraries - Salama, Tarek A. (Synlett, 2013)
A general mild and efficient protocol for the synthesis of amidoalkyl naphthol libraries was achieved utilizing tetrachlorosilane and zinc chloride in dichloromethane at ambient temperature via a one-pot, three-component condensation of various aldehydes, nitriles (amides), and beta-naphthol.
Keywords: amidoalkyl naphthols; combinatorial synthesis; multicomponent reactions; Ritter reaction; tetrachlorosilane

Solvent-free, highly efficient one-pot multi-component synthesis of 1-amido- and 1-carbamato-alkyl naphthols/phenols catalyzed by ethylammonium nitrate as reusable ionic liquid under neat reaction condition at ambient temperature - Mulla, Shafeek Abdul Rashid; Salama, Tarek A.; Pathan, Mohsinkhan Y.; Inamdar, Suleman M.; Chavan, Santosh S. (Tetrahedron Letters, 2013)
A solvent-free, environmentally clean, mild, and simple one-pot multi-component protocol has been developed for the efficient synthesis of 1-amido- and 1-carbamato-alkyl naphthols/phenols in excellent yields via one-pot three-component condensation of various aldehydes, amides/carbamates/urea, and naphthols/phenols using ethylammonium nitrate (EAN) as a reusable ionic liquid catalyst under neat reaction condition at ambient temperature. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: Aldehyde; amide; Carbamate Phenol; Ethylammonium nitrate (EAN); Urea